Virtual communities for elderly healthcare: user-based requirements elicitation. (15th September 2011) - Hermens, Jan-Willem Van 't Klooster; Bert-Jan Van Beijnum; Pravin Pawar; Klaas Sikkel; Lucas Meertens; Hermie
Virtual communities for elderly healthcare have a potential to improve the community building process and to facilitate care services through support for activities, participation and information needs. This paper expounds on this idea by proposing a mobile virtual community (MVC) platform for elderly healthcare based on a services concept. The requirements for this platform are elicited using a method based on in-depth interview sessions with clients and caregivers in a care institution, a workshop with multiple stakeholders, and scenario-based user need analysis. We focus on the technical platform that is intended to fulfil the requirements elicited from this approach. The platform is an extension of our existing MVC platform architecture, based on service-oriented principles. It enables user-tailoring through an adaptable set of mobile and platform services. We describe the platform and discuss its current and novel services as distilled from the requirements elicitation.